FAMILY STRUGGLES AND ITS IMPACT ON PSYCHOLOGICAL WELLBEING OF FIRST-YEAR STUDENTS DURING COVID-19 PANDEMIC - Nur Raihani, Mohd Yusri Azhar (Universiti Malaysia Sarawak (UNIMAS), 2021)
This study explored the family struggles and challenges faced by eight UNIMAS first-year students during COVID-19 pandemic. The purposes are to understand how the pandemic affects the family which then affect student’s psychological wellbeing and to explore the coping strategies used by them to maintain their psychological wellbeing when dealing with these challenges. Participants reported that they experienced family struggles such as financial hardship, relationship problems and having to juggle between their roles as students and children. Despite that, they reported positive aspects of staying at home during the pandemic with their family such as they can strengthen the bond, they get enough care, and they have good support system. Participants also revealed that they face other challenges as first-year students during the pandemic such as academic struggle and personal struggle. Positive Psychology PERMA Model approach was utilised as their coping strategies to maintain their psychological wellbeing during the COVID-19 outbreak which includes the element positive emotions, engagement, relationship, meaning and accomplishment. This study can lead to further implications on the psychological wellbeing of the first-year students in the new normal of public higher education institutions.